2021
DOI: 10.1111/cas.14797
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan 2,3‐dioxygenase in tumor cells is associated with resistance to immunotherapy in renal cell carcinoma

Abstract: Indoleamine 2,3‐dioxygenase 1 (IDO1) is a key enzyme associated with immunomodulation through its regulation of the tryptophan‐kynurenine (Kyn) pathway in advanced cancers, including metastatic renal cell carcinoma (mRCC). However, the failure of IDO1 inhibitors when used in combination with immune checkpoint inhibitors (ICIs), as observed in clinical trials, raises a number of questions. This study aimed to investigate the association of tryptophan 2,3‐dioxygenase (TDO) and IDO1 with cancer development and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The composition of the gut microbiota determines several tryptophan metabolites because they are catabolism products of gut microbiota. These tryptophan-derived microbial catabolites are important signaling molecules in the host and the microorganisms ( 24 , 25 ). Targeted metabolomics studies have shown that RCC patients have elevated Kyn pathway metabolites ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the gut microbiota determines several tryptophan metabolites because they are catabolism products of gut microbiota. These tryptophan-derived microbial catabolites are important signaling molecules in the host and the microorganisms ( 24 , 25 ). Targeted metabolomics studies have shown that RCC patients have elevated Kyn pathway metabolites ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the presence or absence of the immune system in the tumor microenvironment, we can distinguish three immunophenotypes of tumors: (1) "Hot" tumors, which are strongly infiltrated by T lymphocytes and many inflammatory signals are presented; (2) "cold" tumors, which are scanted of any immune cells infiltration nor inflammatory signs; (3) tumors with immune exclusion, where immune cells are at the periphery or within the stromal tissue [10][11][12]. It is postulated that high density of T lymphocytes and pre-existing of primed immune response in "hot" tumors are associated with higher clinical benefits from immunotherapy [10][11][12][13][14][15]. The immunotherapy resistance associated with an impaired function of the immune system, also referred in the literature as tumor extrinsic mechanism, could be considered on several levels of immune system dysfunction and could be associated with specific tumor immunophenotypes [8,16,17].…”
Section: Resistance To Immunotherapy Associated With An Impaired Function Of the Immune Systemmentioning
confidence: 99%
“…However, we should remember that the blood vessels growth into the tumor tissue occurs in a quite disorganized and chaotic manner. This situation of resistance is most commonly associated with the occurrence of tumors with immune exclusion, where immune cells are at the periphery or within the stromal tissue [11,12,15].…”
Section: Resistance To Immunotherapy Associated With An Impaired Function Of the Immune Systemmentioning
confidence: 99%
“…The link between very long chain fatty acid-containing lipids and response to ICI in RCC can be explained by enhanced peroxisome signaling in activated T cells, which leads to a metabolic switch to fatty acid catabolism [104]. Lastly, increased conversion of TRP to kynurenine by IDO leads to inhibition of T cell function and is involved in the regulation of the immunosuppressive TME of mRCC [54,105].…”
Section: Icis Based On Targeting Immunometabolomics In Rcc-bmmentioning
confidence: 99%